Method for forming compact skin layer on surface of PP or PMP hollow fiber membrane

By forming a dense hydrophobic cortex on the surface of the PP or PMP hollow fiber membrane, the polymerization and cross-linking reaction of polymerizable silicone and polyalkyl siloxane are solved, and the effect of improving the anti-wetting performance without reducing the gas flux is achieved.

CN119838434AActive Publication Date: 2025-04-18HANGZHOU BAITENG ENVIRONMENTAL TECH CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510315085.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-18
Publication Date
2025-04-18
Estimated Expiration
2045-03-18

AI Technical Summary

Technical Problem

Existing PP or PMP hollow fiber membranes are prone to wetting when dealing with non-pure water liquids, lose the ability to degass or fill, and reducing the membrane pore size to improve anti-wetting performance will lead to a decrease in gas flux.

Method used

By forming a dense cortex on the surface of the hollow fiber membrane of PP or PMP, polymerizable silicone and polyalkyl siloxane are used for polymerization and cross-linking reactions to form a hydrophobic dense cortex. The method includes cortical solution preparation, cortical coating, cortical alcoholylation and high temperature dehydration polymerization steps.

Benefits of technology

Without significantly reducing the gas flux, the anti-wetting performance of the hollow fiber membrane is significantly improved, the pore size on the membrane surface is reduced without affecting the pore structure inside the membrane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838434A_ABST
    Figure CN119838434A_ABST
Patent Text Reader

Abstract

The invention discloses a method for forming a compact skin layer on the surface of a PP or PMP hollow fiber membrane, which comprises the following steps: mixing polymerizable siloxane, a free radical initiator and a solvent, heating, stirring, cooling to room temperature for later use after complete reaction, adding polyalkyl siloxane with different chain lengths, and uniformly stirring at room temperature to obtain a skin layer solution; immersing the PP or PMP hollow fiber membrane into the skin layer solution, and staying for 0.5-3 hours for skin layer coating; preparing an aqueous solution with the pH value of 2.5-3.6, heating, and immersing the hollow fiber membrane coated with the cortex into the aqueous solution for cortex alcoholysis; and transferring the hollow fiber membrane subjected to cortex alcoholysis into a high-temperature environment, and performing dehydration crosslinking to obtain the hollow fiber membrane with a compact cortex formed on the surface. The hollow fiber membrane prepared by the method disclosed by the invention is obviously improved in wetting resistance on the premise of not greatly reducing the air flux.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hollow fiber membranes, in particular to a method for forming a dense cortex on the surface of a PP or PMP hollow fiber membrane. Background Art

[0002] At present, the industrially produced hollow fiber membrane contactors generally use PP or PMP membrane materials prepared by melt stretching or thermal phase separation as the contact medium. Many dense pores will be formed on their surface during the preparation process for gas transmission. These materials are hydrophobic to prevent liquid from penetrating and wetting across the membrane. However, in actual use, since the liquid treated by the membrane contactor is not pure water, it may be mixed with impurities such as a small amount of alcohol, ester, hydrocarbons and other organic matter or bacterial microorganisms, which makes the membrane easily wetted and loses the ability to degas or add gas. Reducing the membrane pore size can improve the membrane's anti-wetting ability. However, if the membrane pore size is reduced, the gas flux of the membrane will decrease, and the degassing or adding gas ability will decrease.

[0003] Therefore, it is urgent to study how to improve the membrane's anti-wetting performance without significantly reducing the gas flux of PP or PMP hollow fiber membranes. Summary of the invention

[0004] The object of the present invention is to provide a method for forming a dense skin layer on the surface of a PP or PMP hollow fiber membrane, so as to solve the problems raised in the above background technology.

[0005] To achieve the above object, the present invention provides the following technical solution: a method for forming a dense cortex on the surface of a PP or PMP hollow fiber membrane, comprising: S1. Preparation of cortical solution: S1.1, polymerization reaction: the polymerizable siloxane, free radical initiator and solvent are mixed, heated to 60-80°C and stirred, reacted for 7-9 hours, and then cooled to room temperature for use; S1.2, cross-linking reaction: adding polyalkylsiloxanes of different chain lengths to the solution obtained in step S1.1, stirring at room temperature for 1-3 hours to obtain a cortex solution; S2, skin coating: immerse the PP or PMP hollow fiber membrane in the skin solution obtained in step S1, and leave it for 0.5-3h to perform skin coating; S3, cortical alcoholysis: prepare an aqueous solution with a pH of 2.5-3.6, heat it to 75-85°C, immerse the PP or PMP hollow fiber membrane coated with the cortical layer in step S2 and leave it for 0.5-1h to perform cortical alcoholysis; S4, high temperature dehydration polymerization: the PP or PMP hollow fiber membrane after the alcoholysis of the cortex in step S3 is placed in a high temperature environment of 75-85°C for dehydration and crosslinking to obtain a PP or PMP hollow fiber membrane with a dense cortex formed on the surface.

[0006] The present application uses polymerizable siloxane as a monomer in a solvent to carry out a free radical polymerization reaction to obtain polymer A, adds a crosslinking agent polyalkyl siloxane, and dips it on a hollow fiber membrane. An acid aqueous solution is used to cause alcoholysis and crosslinking reactions between polymer A and polyalkyl siloxane. When a solvent slightly soluble in water is used, it is more conducive to the full alcoholysis and crosslinking reactions at the interface. Drying is carried out at a high temperature to complete further crosslinking to form a dense cortex covering the surface of the PP or PMP hollow fiber membrane. After testing, the PP or PMP hollow fiber membrane prepared by the method of the present application has significantly improved the membrane's anti-wetting performance without significantly reducing the gas flux.

[0007] Preferably, the polymerizable siloxane in step S1 is a methoxy- or ethoxy-containing silane with a polymerization site, wherein the polymerization site is a vinyl, acryl or acryloxy group that can form a polymer through a free radical reaction.

[0008] Preferably, the polyalkylsiloxane in step S1 is a methoxy or ethoxy silane containing different numbers of carbon atoms.

[0009] Preferably, the free radical initiator in step S1 is an azo initiator.

[0010] Preferably, the solvent in step S1 is an ester solvent.

[0011] Preferably, the polymerizable siloxane includes one or more of vinyltrimethoxysilane, vinyltriethoxysilane, acryltrimethoxysilane, acryltriethoxysilane, acryloxyethyltrimethoxysilane, acryloxyethyltriethoxysilane, 3-acryloxypropyltrimethoxysilane or 3-acryloxypropyltriethoxysilane.

[0012] Preferably, the polyalkylsiloxane includes one or more of methyltrimethoxysilane, ethyltrimethoxysilane, propyltrimethoxysilane, butyltrimethoxysilane, octyltrimethoxysilane, heptyltrimethoxysilane, dodecyltrimethoxysilane, tetradecyltrimethoxysilane, hexadecyltrimethoxysilane, octadecyltrimethoxysilane, methyltriethoxysilane, ethyltriethoxysilane, propyltriethoxysilane, butyltriethoxysilane, octyltriethoxysilane, heptyltriethoxysilane, dodecyltriethoxysilane, tetradecyltriethoxysilane, hexadecyltriethoxysilane or octadecyltriethoxysilane.

[0013] Compared with the prior art, the beneficial effects of the present invention are: the PP or PMP hollow fiber membrane prepared by the method of the present application has significantly improved anti-wetting performance without significantly reducing the gas flux, can reduce the pores on the surface of the hollow fiber membrane, does not affect the pores inside the hollow fiber, and improves the radial asymmetry of the hollow fiber membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 It is a schematic diagram comparing the contact angles before and after a dense skin layer is formed on the surface of a PP or PMP hollow fiber membrane in an embodiment of the present invention; Figure 2 This is an electron microscope photograph of the PP or PMP hollow fiber membrane before a dense cortex is formed on the surface of the hollow fiber membrane in Example 1 of the present invention; Figure 3 This is an electron microscope photograph of the PP or PMP hollow fiber membrane after a dense cortex is formed on the surface in Example 1 of the present invention. DETAILED DESCRIPTION

[0015] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0016] The present invention provides a method for forming a dense cortex on the surface of a PP or PMP hollow fiber membrane, comprising: S1. Preparation of cortical solution: S1.1. Polymerization reaction: Mix a polymerizable siloxane, a free radical initiator and a solvent, heat to 60-80°C and stir, react for 7-9 hours, and then cool to room temperature for use. The polymerizable siloxane is a methoxy- or ethoxy-containing silane with a polymerization site, wherein the polymerization site is a vinyl, propenyl or acryloxy group that can form a polymer through a free radical reaction, such as vinyltrimethoxysilane, vinyltriethoxysilane, propenyltrimethoxysilane, propenyltriethoxysilane, acryloxyethyltrimethoxysilane, acryloxyethyltriethoxysilane, 3-acryloxypropyltrimethoxysilane or 3-acryloxypropyltriethoxysilane; the free radical initiator is an azo initiator; and the solvent is an ester solvent.

[0017] S1.2, cross-linking reaction: add polyalkylsiloxanes of different chain lengths to the solution obtained in step S1.1, and stir at room temperature for 1-3 hours to obtain a cortex solution, wherein the polyalkylsiloxane is a methoxy or ethoxysilane containing different numbers of carbon atoms, such as methyltrimethoxysilane, ethyltrimethoxysilane, propyltrimethoxysilane, butyltrimethoxysilane, octyltrimethoxysilane, heptyltrimethoxysilane, dodecyltrimethoxysilane, tetradecyltrimethoxysilane, hexadecyltrimethoxysilane, octadecyltrimethoxysilane, methyltriethoxysilane, ethyltriethoxysilane, propyltriethoxysilane, butyltriethoxysilane, octyltriethoxysilane, heptyltriethoxysilane, dodecyltriethoxysilane, tetradecyltriethoxysilane, hexadecyltriethoxysilane or octadecyltriethoxysilane.

[0018] S2, skin coating: immerse the PP or PMP hollow fiber membrane in the skin solution obtained in step S1, and leave it for 0.5-3h to perform skin coating; S3, cortical alcoholysis: prepare an aqueous solution with a pH of 2.5-3.6, heat it to 75-85°C, immerse the PP or PMP hollow fiber membrane coated with the cortical layer in step S2 and leave it for 0.5-1h to perform cortical alcoholysis; S4, high temperature dehydration polymerization: the PP or PMP hollow fiber membrane after the alcoholysis of the cortex in step S3 is placed in a high temperature environment of 75-85°C for dehydration and crosslinking to obtain a PP or PMP hollow fiber membrane with a dense cortex formed on the surface.

[0019] Taking vinyltriethoxysilane as an example, the reaction process of step S1.1 is as follows: .

[0020] The reaction process of step S1.2 is as follows: .

[0021] The reaction process of step S3 is as follows: .

[0022] The reaction process of step S4 is as follows: . Embodiment 1

[0023] The following reagents were added to a three-necked flask: 10 g of vinyl triethoxysilane, 0.1 g of azobisisobutyronitrile and 100 g of ethyl acetate, heated to 70°C and stirred, reacted for 8 hours, and then cooled to room temperature for use; 5 g of octadecyl triethoxysilane was added to the three-necked flask and stirred for 1 hour to obtain a cortex solution; the PP or PMP hollow fiber membrane was immersed in the cortex solution and kept for 3 hours for cortex coating; an aqueous solution with a pH of 3 was prepared, heated to 70°C, and the PP or PMP hollow fiber membrane after the cortex coating was immersed and kept for 3 hours for cortex alcoholysis; the PP or PMP hollow fiber membrane after the alcoholysis was transferred to an oven at 80°C and kept for 1 hour for dehydration and cross-linking to obtain a PP or PMP hollow fiber membrane with a dense cortex formed on the surface. Embodiment 2

[0024] The following reagents were added into a three-necked flask: 15 g of vinyl trimethoxysilane, 0.1 g of azobisisobutyronitrile and 100 g of triethyl phosphate, heated to 80°C and stirred, reacted for 8 hours, and then cooled to room temperature for use; 3 g of n-decyltriethoxysilane was added into the three-necked flask, stirred for 1 hour to obtain a cortex solution; the PP or PMP hollow fiber membrane was immersed in the cortex solution and kept for 3 hours for cortex coating; an aqueous solution with a pH of 3 was prepared, heated to 70°C, and the PP or PMP hollow fiber membrane after the cortex coating was immersed and kept for 3 hours for cortex alcoholysis; the PP or PMP hollow fiber membrane after the alcoholysis was transferred to an oven at 80°C and kept for 1 hour for dehydration and cross-linking to obtain a PP or PMP hollow fiber membrane with a dense cortex formed on the surface. Embodiment 3

[0025] The following reagents were added into a three-necked flask: 12 g of acryloxyethyltrimethoxysilane, 0.1 g of azobisisobutyronitrile and 100 g of butyl acetate, heated to 60°C and stirred, reacted for 8 hours, and then cooled to room temperature for use; 6 g of ethyltrimethoxysilane was added into the three-necked flask and stirred for 1 hour to obtain a cortex solution; the PP or PMP hollow fiber membrane was immersed in the cortex solution and kept for 0.5 hour for cortex coating; an aqueous solution with a pH of 3 was prepared, heated to 70°C, and the PP or PMP hollow fiber membrane after the cortex coating was immersed and kept for 3 hours for cortex alcoholysis; the PP or PMP hollow fiber membrane after the alcoholysis was transferred to an oven at 80°C and kept for 1 hour for dehydration and crosslinking to obtain a PP or PMP hollow fiber membrane with a dense cortex formed on the surface. Embodiment 4

[0026] The following reagents were added into a three-necked flask: 16 g of 3-acryloxypropyltrimethoxysilane, 0.12 g of azobisisobutyronitrile and 100 g of butyl acetate, heated to 60°C and stirred, reacted for 8 hours, and then cooled to room temperature for use; 3 g of tetradecyltrimethoxysilane was added into the three-necked flask, stirred for 1 hour to obtain a cortex solution; the PP or PMP hollow fiber membrane was immersed in the cortex solution and kept for 0.5 hour for cortex coating; an aqueous solution with a pH of 3 was prepared, heated to 70°C, and the PP or PMP hollow fiber membrane after the cortex coating was immersed and kept for 3 hours for cortex alcoholysis; the PP or PMP hollow fiber membrane after the alcoholysis was transferred to an oven at 80°C and kept for 1 hour for dehydration and crosslinking to obtain a PP or PMP hollow fiber membrane with a dense cortex formed on the surface. Embodiment 5

[0027] The following reagents were added into a three-necked flask: 16 g of vinyltrimethoxysilane, 0.12 g of azobisisobutyronitrile and 100 g of butyl acetate, heated to 60°C and stirred, reacted for 8 hours, and then cooled to room temperature for use; 6 g of tetradecyltrimethoxysilane was added into the three-necked flask, stirred for 1 hour to obtain a cortex solution; the PP or PMP hollow fiber membrane was immersed in the cortex solution and kept for 0.5 hour for cortex coating; an aqueous solution with a pH of 3 was prepared, heated to 70°C, and the PP or PMP hollow fiber membrane after the cortex coating was immersed and kept for 3 hours for cortex alcoholysis; the PP or PMP hollow fiber membrane after the alcoholysis was transferred to an oven at 80°C and kept for 1 hour for dehydration and cross-linking to obtain a PP or PMP hollow fiber membrane with a dense cortex formed on the surface.

[0028] The PP or PMP hollow fiber membranes with dense skin layers formed on the surface prepared in Examples 1 to 5 were tested for contact angle, air flux and water immersion pressure. The results are shown in the following table: .

[0029] like Figure 1-3 As shown, using different polymerizable siloxanes, initiators and polyalkyl siloxanes can prepare dense hydrophobic surfaces with different properties. Generally speaking, polyalkyl siloxanes with longer carbon chains can provide stronger hydrophobic effects. This is because the long carbon chains of polyalkyl groups have lower surface energy and greater repulsion to water, which shows better hydrophobic effects. At the same time, increasing the amount of polymerizable siloxane and polyalkyl siloxane, or increasing the cross-linking temperature, can form polymers with larger molecular weights, which is more conducive to the formation of a dense cross-linked structure of the coating. Compared with the unmodified PP hollow fiber, the hollow fiber membrane prepared by this method showed a stronger hydrophobic effect, and the surface water contact angle was greatly increased from 97° to a maximum of about 128 degrees, forming a super hydrophobic surface. At the same time, this method also increases the water immersion pressure without significantly reducing the gas flux, which is also effective evidence for the formation of a dense layer of the hydrophobic coating.

[0030] In summary, the PP or PMP hollow fiber membrane treated by this method forms a dense hydrophobic cortex on the surface of the fiber membrane, which increases the water immersion pressure, makes it more difficult for pollutants to infiltrate the membrane fibers, and greatly improves the hydrophobicity. At the same time, the gas flux is not greatly reduced, the growth of the dense cortex does not spread to the radial depth of the hollow fiber membrane, and the original numerous and dense gas channels are retained. According to the test results, this application does not reduce the pore size of the hollow fiber membrane, but applies a layer of hydrophobic dense cortex on its surface, which can effectively reduce the membrane pore size on the outside of the membrane without affecting the radial pores of the hollow fiber membrane. This type of cortex should have a high degree of density, a high air permeability, is not easy to fall off and will not penetrate into the interior of the membrane.

[0031] Polymerizable siloxanes have polymerizable vinyl, propylene, and acryloyloxyethyl groups, and can easily and quickly undergo free radical polymerization to generate polymers. After the polymerization reaction is completed, polyalkyl siloxane is used for mixing. Under acidic conditions, the methoxy and ethoxy groups of the polymer and polyalkyl siloxane are hydrolyzed to generate cross-linkable silanol bonds and methyl and ethanol groups. The silanol bonds are mutually condensed and dehydrated to form siloxy-silicon bonds and tightly cross-linked. During the drying process, the silanols are further dehydrated and condensed, and the degree of cross-linking is further improved. At the same time, the polyalkyl chain also provides hydrophobicity, making the coating more hydrophobic and further improving the contact angle. Due to the cross-linking reaction, the polymers and cross-linking agents between different molecular chains are fixed to each other and will not fall off during use.

[0032] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for forming a dense cortex on the surface of a PP or PMP hollow fiber membrane, characterized in that: include: S1. Preparation of cortical solution: S1.1, polymerization reaction: the polymerizable siloxane, free radical initiator and solvent are mixed, heated to 60-80°C and stirred, reacted for 7-9 hours, and then cooled to room temperature for use; S1.2, cross-linking reaction: adding polyalkylsiloxanes of different chain lengths to the solution obtained in step S1.1, stirring at room temperature for 1-3 hours to obtain a cortex solution; S2, skin coating: immerse the PP or PMP hollow fiber membrane in the skin solution obtained in step S1, and leave it for 0.5-3h to perform skin coating; S3, cortical alcoholysis: prepare an aqueous solution with a pH of 2.5-3.6, heat it to 75-85°C, immerse the PP or PMP hollow fiber membrane coated with the cortical layer in step S2 and leave it for 0.5-1h to perform cortical alcoholysis; S4, high temperature dehydration polymerization: the PP or PMP hollow fiber membrane after the alcoholysis of the cortex in step S3 is placed in a high temperature environment of 75-85°C for dehydration and crosslinking to obtain a PP or PMP hollow fiber membrane with a dense cortex formed on the surface.

2. The method for forming a dense cortex on the surface of a PP or PMP hollow fiber membrane according to claim 1, characterized in that: The polymerizable siloxane in step S1 is a methoxy- or ethoxy-containing silane with a polymerization site, wherein the polymerization site is a vinyl, acryl or acryloxy group that can form a polymer through a free radical reaction.

3. The method for forming a dense cortex on the surface of a PP or PMP hollow fiber membrane according to claim 1 or 2, characterized in that: In step S1, the polyalkylsiloxane is a methoxy or ethoxy silane containing different numbers of carbon atoms.

4. The method for forming a dense cortex on the surface of a PP or PMP hollow fiber membrane according to claim 1 or 2, characterized in that: In step S1, the free radical initiator is an azo initiator.

5. The method for forming a dense cortex on the surface of a PP or PMP hollow fiber membrane according to claim 1 or 2, characterized in that: The solvent in step S1 is an ester solvent.

6. The method for forming a dense cortex on the surface of a PP or PMP hollow fiber membrane according to claim 2, characterized in that: The polymerizable siloxane includes one or more of vinyltrimethoxysilane, vinyltriethoxysilane, acryltrimethoxysilane, acryltriethoxysilane, acryloxyethyltrimethoxysilane, acryloxyethyltriethoxysilane, 3-acryloxypropyltrimethoxysilane or 3-acryloxypropyltriethoxysilane.

7. The method for forming a dense cortex on the surface of a PP or PMP hollow fiber membrane according to claim 3, characterized in that: The polyalkylsiloxane includes one or more of methyltrimethoxysilane, ethyltrimethoxysilane, propyltrimethoxysilane, butyltrimethoxysilane, octyltrimethoxysilane, heptyltrimethoxysilane, dodecyltrimethoxysilane, tetradecyltrimethoxysilane, hexadecyltrimethoxysilane, octadecyltrimethoxysilane, methyltriethoxysilane, ethyltriethoxysilane, propyltriethoxysilane, butyltriethoxysilane, octyltriethoxysilane, heptyltriethoxysilane, dodecyltriethoxysilane, tetradecyltriethoxysilane, hexadecyltriethoxysilane or octadecyltriethoxysilane.

Citation Information

Patent Citations

  • Preparation method of high-performance hollow-fiber organic gas separation composite membrane

    CN107126847A